Pelatihan Pencatatan Transaksi Keuangan Berbasis Android untuk UMKM di Desa Bojong Kulur - Bogor - Weli Weli; Syarief Darmoyo (LP2M INSURI Ponorogo, 2026)
This training was conducted to address the needs of MSMEs in Bojong Kulur Village, Bogor, regarding digital bookkeeping. Although MSME owners in Bojong Kulur Village had previously attended several accounting training sessions, MSMEs still faced obstacles in consistently recording financial transactions. The purpose of the activity is to introduce an Android-based bookkeeping application for MSMEs. The activity was carried out at the Bojong Kulur Village Hall. The method used is a presentation accompanied by practice using the SiApik Android application. In addition, a simulation using video recordings includes usage guidelines at the end of the activity, before participants fill out the activity evaluation. The training participants were 71 MSME owners. The purpose of this training is for each participant to record financial transactions using a free Android-based application consistently. The evaluation results showed that participants felt the benefits of using the SiApik application, and overall, the training activities were considered good. However, participants' suggestions indicated that they needed individual assistance in applying it to their companies. Another suggestion is that training on calculating production costs is necessary. This suggestion will be followed up on in the next activity.